2023
DOI: 10.1021/acs.organomet.2c00563
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Regio- and Stereoselective Hydrosilylation of Alk-2-ynes with Tertiary Silanes

Abstract: Selectivity control in the addition reactions of internal alkynes that bear two similar substituents presents a big challenge in modern organic synthesis. Herein we report that β-(E)-selective hydrosilylation of alk-2-ynes with tertiary silanes can be achieved by using Co 2 (CO) 8 as the catalyst. Under the catalytic reaction conditions, a wide range of alk-2-ynes can be converted into vinylsilanes with the β-(E) isomers as the major or sole hydrosilylation products. Mechanistic studies suggest that alkynebrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Interestingly, for Co-catalyzed hydrosilylation of alkynes, the phenomenon of an extraordinary ligand control over the reaction pathway offers to receive all of the plausible regio-and/or stereoisomers, e. g., β-(E)-, [26,[41][42][43][44] β-(Z)-, [45] and α-vinylsilanes. [33,[35][36][37][38][39][40][41][42][43][44] However, to the best of our knowledge, there were no protocols describing the use of the triazine-based PNP-Co catalysts in the hydrosilylation of alkynes. Please take note that these specific complexes exhibit extraordinary catalytic activity in several processes, thereby providing access to a variety of important organic molecules.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, for Co-catalyzed hydrosilylation of alkynes, the phenomenon of an extraordinary ligand control over the reaction pathway offers to receive all of the plausible regio-and/or stereoisomers, e. g., β-(E)-, [26,[41][42][43][44] β-(Z)-, [45] and α-vinylsilanes. [33,[35][36][37][38][39][40][41][42][43][44] However, to the best of our knowledge, there were no protocols describing the use of the triazine-based PNP-Co catalysts in the hydrosilylation of alkynes. Please take note that these specific complexes exhibit extraordinary catalytic activity in several processes, thereby providing access to a variety of important organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Given our recent success in incorporating readily available and cost‐effective cobalt complexes into organometallic synthesis, we hypothesized that an appropriate catalytic system could serve as a sustainable platform for producing diverse libraries of vinylsilanes [51–53] . Significantly, the subject of Co‐catalyzed hydrosilylation for internal alkynes, especially symmetrical ones, was limited to a few examples up until now [32,33,38–46] . As far as we know, only four research groups have reported satisfactory results to date, specifically regarding diaryl and bis‐aliphatic symmetrical internal alkynes [34–37,39,43] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations